2019
DOI: 10.18632/aging.102388
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of long non-coding RNA H19 downregulates CTCF to protect against atherosclerosis by upregulating PKD1 expression in ApoE knockout mice

Abstract: This study aimed to explore the interactions among long non-coding RNA H19, transcriptional factor CCCTC-binding factor (CTCF) and polycystic kidney disease 1 (PKD1), and to investigate its potentially regulatory effect on vulnerable plaque formation and angiogenesis of atherosclerosis. We established an atherosclerosis mouse model in ApoE knockout mice, followed by gain- and loss-of-function approaches. H19 was upregulated in aortic tissues of atherosclerosis mice, but silencing of H19 significantly inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The VEGF family includes several members: VEGF-A, −B, −C, −D, −E, and -F and placental growth factor (PlGF) (Hoeben et al 2004 ). In aortic tissues of atherosclerotic mice, knockdown of lncRNA-H19 prevents intraplaque angiogenesis and downregulates the expression of the angiogenesis-related factors matrix metalloproteinase 2 (MMP-2) and VEGF (Yang et al 2019 ). In contrast, lncRNA-H19 overexpression recruits CCCTC-binding factor (CTCF) to repress the polycystic kidney disease 1 (PKD1) gene (Yang et al 2019 ), mutations of which may lead to angiogenesis (Li et al 2003 ).…”
Section: Lncrna-h19 and The Pathophysiology Of Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…The VEGF family includes several members: VEGF-A, −B, −C, −D, −E, and -F and placental growth factor (PlGF) (Hoeben et al 2004 ). In aortic tissues of atherosclerotic mice, knockdown of lncRNA-H19 prevents intraplaque angiogenesis and downregulates the expression of the angiogenesis-related factors matrix metalloproteinase 2 (MMP-2) and VEGF (Yang et al 2019 ). In contrast, lncRNA-H19 overexpression recruits CCCTC-binding factor (CTCF) to repress the polycystic kidney disease 1 (PKD1) gene (Yang et al 2019 ), mutations of which may lead to angiogenesis (Li et al 2003 ).…”
Section: Lncrna-h19 and The Pathophysiology Of Atherosclerosismentioning
confidence: 99%
“…In aortic tissues of atherosclerotic mice, knockdown of lncRNA-H19 prevents intraplaque angiogenesis and downregulates the expression of the angiogenesis-related factors matrix metalloproteinase 2 (MMP-2) and VEGF (Yang et al 2019 ). In contrast, lncRNA-H19 overexpression recruits CCCTC-binding factor (CTCF) to repress the polycystic kidney disease 1 (PKD1) gene (Yang et al 2019 ), mutations of which may lead to angiogenesis (Li et al 2003 ). VEGF-A has been certified as a target of microRNA-199a-5p (miR-199a-5p) (Hsu et al 2014 ).…”
Section: Lncrna-h19 and The Pathophysiology Of Atherosclerosismentioning
confidence: 99%
“…APOC1 is a member of the apolipoprotein family that ACTS not only to transport lipids and stabilize the lipoprotein structure but also to regulate pathological processes including diabetes, Alzheimer's and inflammation. [11][12][13][14] In recent years, some studies have found that ApoA1, 15,16 ApoB, [17][18][19] ApoE 20,21 and other apolipoproteins 22 are abnormally expressed in tumors and are related to the prognosis of patients. Therefore, the role of apolipoprotein family in the occurrence and development of tumors has attracted more attention.…”
Section: Introductionmentioning
confidence: 99%
“…While H19 expression decreases in ECs of aging mice, 6 increased H19 expression in SMCs induces aortic aneurysm in animal models 7,8 . In an ApoE knockout (KO) atherosclerosis mouse model, upregulation of H19 expression was observed in aortic tissues (likely in both ECs and SMCs) and silencing H19 using antisense oligonucleotides attenuated disease progression 9 . Collectively, these findings suggest a causal role of H19 expression in ECs/SMCs in the pathogenesis of CVD.…”
Section: Introductionmentioning
confidence: 92%